Piperlongumine inhibits neuroinflammation via regulating NF-κB signaling pathways in lipopolysaccharide-stimulated BV2 microglia cells - Namkwon Kim; Jimin Do; Jae-sung Bae; Hee Kyung Jin; Jong-Ho Kim; Kyung-Soo Inn; Myung Sook Oh; Jong Kil Lee (Elsevier, 2018)
Inflammatory processes in the central nervous system are feature among biological reactions to harmful stimuli such as pathogens and damaged cells. In resting conditions, microglia are involved in immune surveillance and brain homeostasis. However, the activation of abnormal microglia can be detrimental to neurons, even resulting in neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and Huntington's disease. Therefore, normalization of microglial activation is considered a promising strategy for developing drugs that can treat or prevent inflammation-related brain diseases. In the present study, we investigated the effects of piperlongumine, an active component of Piper longum, on lipopolysaccharide (LPS)-induced neuroinflammation using BV2 microglial cells. We found that piperlongumine significantly inhibited the production of nitric oxide and prostaglandin E2 induced by LPS. Piperlongumine also reduced the expression of inducible nitric oxide synthase and cyclooxygenase-2 as well as proinflammatory cytokines such as tumor necrosis factor-α and interleukin-6. Piperlongumine exerted its anti-neuroinflammatory effects by suppressing the nuclear factor kappa B signaling pathway. These findings suggest that piperlongumine could be a candidate agent for the treatment of inflammation-related neurodegenerative diseases. Keywords: Piperlongumine, Piper longum, Neuroinflammation, Microglia, Lipopolysaccharide